THE ROLE OF PERFUSION IN THE AGE-ASSOCIATED DECLINE OF MITOCHONDRIAL FUNCTION WITH AGING IN HEALTHY INDIVIDUALS. (11th November 2018) - Adelnia, F; Cameron, D; Bergeron, C; Fishbein, K; Spencer, R; Reiter, D; Ferrucci, L
Abstract: Maximum in vivo oxidative capacity of skeletal muscle declines with age, and this negatively affects both muscle strength and walking speed. However, it remains unclear whether the loss of oxidative capacity is caused by reduced volume and function of mitochondria or limited substrate availability secondary to impaired perfusion. We sought to elucidate the role of impaired perfusion on the age-related decline of oxidative capacity in 71 participants (44 men, 22–87 years) from an Intramural National Institute on Aging population study. This study enrolls healthy subjects across a wide age range who are subjected to a large panel of functional and biochemical tests. Maximum oxidative capacity was assessed by phosphorus magnetic resonance spectroscopy (31P-MRS) in the mid-thigh (vastus lateralis) of the left leg as post-exercise phosphocreatine (PCr) recovery time (τPCr), with longer τPCr reflecting lower oxidative capacity. Resting muscle perfusion was characterized using a customized diffusion-weighted MRI method based on a formalism that describes superdiffusive transport of blood through tissue. We found both oxidative capacity and perfusion were significantly lower at older age (p<0.05). Maximum oxidative capacity and muscle perfusion were significantly correlated, and this correlation remained significant after introducing age as a covariate; however, the size of the age regression coefficient was substantially diminished (36% decline) and no longer significant (p=0.15). These findings suggest that part of the decline in muscle oxidative capacity observed with aging is due to impaired perfusion. Therefore, resting muscle perfusion represents a therapeutic target for the restoration of oxidative capacity in older persons.